A New Royal Name Sealing from Tell Edfu - Moeller, Nadine (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
The recent excavations at Tell Edfu have led to the discovery of a new Middle Kingdom sealing which was found in an administrative building. It shows the standing figure of the king wearing the crown of Upper and Lower Egypt and has a small cartouche in front of his face that can be read as the throne name of Amenemhat III. This is the first time that such a motif has been discovered in a secure late Middle Kingdom context.